Comparison of explicit and incidental learning strategies in memory-impaired patients - Smith, Christine N. (National Academy of Sciences, 2014)
Declarative memory for rapidly learned, novel associations is thought to depend on structures in the medial temporal lobe (MTL), whereas associations learned more gradually can sometimes be supported by nondeclarative memory and by structures outside the MTL. A recent study suggested that even rapidly learned associations can be supported by structures outside the MTL when an incidental encoding procedure termed “fast mapping” (FM) is used. We tested six memory-impaired patients with bilateral damage to hippocampus and one patient with large bilateral lesions of the MTL. Participants saw photographs and names of animals, plants, and foods that were previously unfamiliar (e.g., mangosteen). Instead of asking participants to study name–object pairings for a later memory test (as with traditional memory instructions), participants answered questions that allowed them to infer which object corresponded to a particular name. In a second condition, participants learned name–object associations of unfamiliar items by using standard, explicit encoding instructions (e.g., remember the mangosteen). In FM and explicit encoding conditions, patients were impaired (and performed no better than a group that was given the same tests but had not previously studied the material). The same results were obtained in a second experiment that used the same procedures with modifications to allow for more robust learning and more reliable measures of performance. Thus, our results with the FM procedure and memory-impaired patients yielded the same deficits in learning and memory that have been obtained by using other more traditional paradigms.